2021
DOI: 10.1002/clen.202100061
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution and Contamination of Soil Mercury in Karst Catchment, Southwest China: Land‐Use Type Influence

Abstract: The policy-driven "Grain for Green Programme" (GGP) has resulted in large-scale land conversion from agricultural land to natural land in the karst area. One research surrounding the GGP is focused on evaluating its ecological implications for total mercury (THg) enrichment in Yinjiang County, Guizhou Province, Southwest China. Results show that 1) THg content in agricultural land (201.85 ± 57.23 µg kg −1 ) is lower compared to the forest (1048.62 ± 306.19 µg kg −1 ) and shrub (2582.60 ± 614.76 µg kg −1 ). 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…HCO 3 − and Ca 2+ concentrations dominated the anions and cations in river water, respectively. Water quality is closely linked to environmental safety and human health [50][51][52]. The urbanization of the Xiaojiang River basin has reached 39.4%, with a total population of nearly 300,000 [39].…”
Section: Hydrochemical Characteristics Of Xiaojiang Rivermentioning
confidence: 99%
“…HCO 3 − and Ca 2+ concentrations dominated the anions and cations in river water, respectively. Water quality is closely linked to environmental safety and human health [50][51][52]. The urbanization of the Xiaojiang River basin has reached 39.4%, with a total population of nearly 300,000 [39].…”
Section: Hydrochemical Characteristics Of Xiaojiang Rivermentioning
confidence: 99%
“…Understanding the distribution patterns of soil mercury and the factors that in uence it is crucial for preventing and managing mercury pollution. Research in karst catchments in the southwestern region showed that soil mercury content varied signi cantly among different land-use types 33 . Agricultural areas had higher mercury levels compared to forest and grassland areas.…”
Section: Statistical Analysis Methodsmentioning
confidence: 99%